Biocompatibility, biomineralization, and maturation of collagen by rtr®, bioglass and dm bone® materials - Benetti, Francine [UNESP] (2020)
This study evaluated the biocompatibility, biomineralization, and collagen fiber maturation induced by Resorbable Tissue Replacement (RTR®; β-tricalcium phosphate [TCP]), Bioglass (BIOG; bioactive glass), and DM Bone® (DMB; hydroxyapatite and β-TCP) in vivo. Sixty-four polyethylene tubes with or without (control group; CG) materials (n=8/group/period) were randomly implanted in the subcutaneous tissue of 16 male Wistar rats (four per rat), weighting 250 to 280 g. The rats were killed after 7 and 30 days (n=8), and the specimens were removed for analysis of inflammation using hematoxylin-eosin; biomineralization assay using von Kossa (VK) staining and polarized light (PL); and collagen fiber maturation using picrosirius red (PSR). Nonparametric data were statistically analyzed by Kruskal-Wallis and Dunn tests, and parametric data by one-way ANOVA test (p<0.05). At 7 days, all groups induced moderate inflammation (p>0.05). At 30 days, there was mild inflammation in the BIOG and CG, and moderate inflammation in the RTR and DMB groups, with a significant difference between the CG and RTR (p<0.05). The fibrous capsule was thick at 7 days and predominantly thin at 30 days in all groups. All materials exhibited structures that stained positively for VK and PL. Immature collagen fibers were predominant at 7 and 30 days in all groups (p>0.05), although DMB exhibited more mature fibers than BIOG at 30 days (p<0.05). RTR, BIOG, and DMB were biocompatible, inducing inflammation that reduced over time and biomineralization in the subcutaneous tissue of rats. DMB exhibited more mature collagen fibers than BIOG over a longer period.